Peran Koperasi Pertanian Mitra Usaha Tani terhadap Pendapatan Usahatani di Kelurahan Landasan Ulin Utara Kecamatan Liang Anggang Kota Banjarbaru Kalimantan Selatan - Lisa Angraini; Usamah Hanafie; Hairi Firmansyah (Universitas Lambung Mangkurat, 2013)
The succeed of a cooperative in achieving the goals is highly relied on the members activities, whether they can cooperate, have work spirit, and obeying all rules and guidance decided on member meeting. The purpose of joining the cooperative is to achieve common goal, that is income increase Thus, the increase of members' income should become the cooperative concern. The study is aimed to: (1) describe the micro finance institution on the cooperative; (2) explore the role of micro finance institution in increasing the farming income; and (3) identify the obstacles faced by the micro finance. The respondents involved were 60 members and non-member of Koperasi Pertanian Mitra Usaha Tani, Kelurahan Landasan Ulin Utara, Kecamatan Liang Anggang, Kata Banjarbaru, Kalimantan Selatan. As located in the middle of agricultural area, the cooperative provides easy credit access to the farmers in nearby area. The credit aid has increased the members' income signifi cantly compared to the non-members'. However, several problems should be settled include limited human resources to manage the cooperative, financial limitation, delay of credit payment, and the work spirit decrease among to committees